Enhanced high-open circuit voltage in fluorinated benzoselenadiazole-based polymer solar cells. (May 2016) - Wang, She-Yu; Liu, Zhi-Yang; Ai, Ling; Islam, Amjad; Peng, Rui-Xiang; Zhang, Jian-Feng; Ge, Zi-Yi
Three new donor–acceptor copolymers (PCDTBSe, PCDTFBSe, and PCDTDFBSe) were designed and synthesized with 2, 7-carbazole as the donor (D) unit and benzoselenadiazole (BSe), monofluoro-benzoselenadiazole, and difluoro-benzoselenadiazole as the acceptor (A) units, respectively. The structure–property relationship of these polymers was elucidated in bulk heterojunction polymer solar cells. All the polymers were fully characterized and exhibited good thermal stability and broad absorption. The highest occupied molecular orbitals (HOMOs) of the PCDTBSe (−5.29 eV), PCDTFBSe (−5.32 eV), and PCDTDFBSe (−5.35 eV) were decreased by incorporating fluorine atoms on the polymer backbone. The low-lying HOMO energy level suggested that the polymers would exhibit high open circuit voltage ( V OC ) when blended with fullerene as the electron acceptor. Solar cell based on PCDTFBSe displayed a power conversion efficiency of 1.09% with a short-circuit current density ( J SC ) of 4.29 mA cm −2, a V OC of 0.78 V, and a fill factor (FF) of 32.51%, under the illumination of AM1.5G, 100 mW cm −2 .